Pemantapan Keterampilan Dasar Mengajar Calon Guru Pendidikan Agama Islam dengan Pedagogi Multiliteracy pada Program Studi Pendidikan Agama Islam Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto - Muhammad Munib (PROGRESSA: Journal of Islamic Religious Instruction, 2018)
The teacher must control the environment as an important part of the process that occurs in the black box, it still must be an important part so that there is not one second that is not useful for the child, since they entered the school gate. Preparation in class, in class, rest periods and also their time at the house of worship, even when they are in the school canteen, are productive times to change their behavior, both ways of thinking, behaving and acting, or even increasing skills and their skills. Based on the focus of the study, this study aims to describe the strengthening of basic teaching skills of Islamic Religious Education teacher candidates with multiliteracy pedagogy in the Islamic Education Study Program at the Raden Wijaya Tarbiyah College of Education in Mojokerto. This research is "Library Research". The research data used is secondary data. The data collection technique used by the authors in this study is documentation. Data processing is carried out by conducting study activities, verification and reduction, grouping and systematization, and interpretation or interpretation so that a phenomenon has social, academic, and scientific value. From the results of the discussion it can be concluded that the strengthening of the basic teaching skills of Islamic Religious Education teacher candidates with multiliteracy pedagogy in the Raden Wijaya Mojokerto Islamic School of Higher Education Islamic Studies Study Program is to make prospective teachers effective. To be an effective teacher must be able to motivate and support students so that they are well equipped to face every challenge given to them both academically and vice versa. With all of the above skills, you will always get an effective teacher degree that inspires students in more than one way